Effect of Reproductive Health Education on Teenagers Through Video Media on Knowledge and Attitudes Regarding Sexual Pre-Marriage in SMPN 1 Dente Teladas - Amelia Heni; Putri Azzahroh; Vivi Silawati (Rajaki of Tulip Medika Publisher, 2024)
Premarital sex is contact between partners of the opposite or same sex, for example holding hands, kissing lips, kissing cheeks, petting, and having intimate relations, which is carried out without the legal ties of marriage according to religion and marriage law. The aim of this research is to determine the effect of reproductive health education on adolescent knowledge and attitudes about premarital sex in junior high school students. The type of research used is experimental research using a pretest-posttest design. The sample in this study was 98 students consisting of 49 experimental groups and 49 control groups. Data collection uses a questionnaire. Data analysis used the Wilxocon test. From the research results, it was found that the average knowledge of teenagers before being given education in the intervention group was 5.9 after being given education was 10.7 , in the control group it was 6.1 before and after 7.3 . The average attitude of adolescents before being given education in the intervention group was 23.8 and after being given education was 37.5. in the control group it was 23.9 and after administration in the control group it was 26.8 . There was an influence in the intervention group and the control group after being given and not being given educational video media on adolescent reproductive health on knowledge and attitudes about premarital sex at SMP N 1 Dente Teladas Tulang Bawang Lampung (p-value = 0.000). There was a difference in knowledge between the intervention and control groups of 44.82, while the difference in attitudes between the intervention and control groups was 49.0 (p-value = 0.000). It is hoped that education will be provided on an ongoing basis in schools .